Resistance and abolition in the borderlands: confronting Trump's reign of terror - Aldama, Arturo J.; Ordaz, Jessica; Chavez, Leo R.; Chávez, Karma R. (The University of Arizona Press, 2024)
"An interdisciplinary collection of cultural, historic, activist, and artistic essays that discuss the impacts of Trump's policies and rhetorics towards BIPoC/Latinx migrants"--